Inter-strand resistance and AC loss in resin-filler impregnated ReBCO Roebel cables. (16th October 2019) - Gao, P; Dhallé, M; van Nugteren, B; Norder, H; Kario, A; Otten, S; Goldacker, W; van Nugteren, J; Kirby, G; de Rijk, G; Bottura, L; Rossi, L; et al.
Abstract: In the frame of the EuCARD2 collaboration, aimed at developing the technology for 20 T class accelerator magnets, several demonstrator dipole magnets are being built using high critical current density and fully transposed ReBCO tape-based Roebel-type cables. In accelerator magnets the dynamic magnetic field quality is one of the key parameters, which is affected by the effective inter-strand resistances in the cables. For this reason, measurements of the inter-strand resistances on ReBCO Roebel cables were carried out at 4.2 and 77 K. Acquiring these data is also essential for input of cable simulation models. The cable samples are impregnated with epoxy resin to reduce the effect of transverse stress degradation due to Lorentz forces acting on the strands in the Roebel cables. The measured inter-strand resistance is used to estimate the AC coupling loss in different magnetic field orientations. Moreover, the contributions of diverse interface contact resistances to overall inter-strand resistance of Roebel cables were determined using a novel theoretical model. For validation, the AC loss of cables were examined in various orientations of applied field at 4.2 K. With three analytical models the hysteresis loss was calculated and compared to the measured data. The average inter-strand resistance of the cable samples impregnated with the unfilled epoxy CTD-101K range from 3 to 16 μ Ω at 77 K and 1.5 to 9 μ Ω at 4.2 K. Between the tapes the copper to copper interface resistance dominates the inter-strand resistance of impregnated Roebel cables. The calculated and measured AC loss for the CTD-101K impregnated Roebel cable lead to equivalent conclusions that the coupling loss is lower than the hysteresis loss within the range of the experiment. These observations substantially differ from earlier results extracted from a similar cable but impregnated with the alumina-filled epoxy resin CTD-101G, which showed considerable coupling loss when exposed to magnetic field parallel the wide face of the cable.